The Origins of Voluntary Compliance: Attitudes toward Taxation in Urban Nigeria. Issue 1 (10th September 2014) - Bodea, Cristina; LeBas, Adrienne
Abstract : Voluntary compliance is an important aspect of strong tax regimes, but there is limited understanding of how social norms favoring compliance emerge. Using novel data from urban Nigeria, where tax enforcement is weak, this article shows that individuals with a positive experience of state services delivery are more likely to express belief in an unconditioned citizen obligation to pay tax. In addition to support for this fiscal exchange mechanism, social context is consequential. Where individuals have access to community-provided goods, which may substitute for effective state services provision, they are less likely to adopt pro-compliance norms. Finally, the article shows that norm adoption increases tax payment. These findings have broad implications for literatures on state formation, taxation and public goods provision.